PERSEPSI GURU TENTANG KOMPETENSI PROFESIONAL GURU DI SEKOLAH MENENGAH KEJURUAN NEGERI SEKECAMATAN PADANG BARAT - Desfitri Ramadhani; Novriyanti Achyar; Hadiyanto; Tia Ayu Ningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe teachers' perceptions regarding professional competence among teachers at state vocational high schools (SMK Negeri) in the Padang Barat District. This is a quantitative descriptive study. The population consisted of 145 teachers, with a sample of 108 teachers selected using the Proportional Random Sampling technique. The research instrument was a Likert-scale questionnaire that had undergone validity and reliability testing. Data were analyzed using descriptive statistics by calculating the mean score. The results indicate that teachers' perceptions of professional competence at state vocational high schools in the Padang Barat District fall into the "Highly Competent" category, with an overall mean score of 4.54. An analysis of specific indicators revealed the following: (1) the indicator for mastering the subject matter taught obtained a mean score of 4.71 (Highly Competent); (2) the indicator for creatively developing learning materials obtained a mean score of 4.26 (Competent); and (3) the indicator for continuous professional development obtained a mean score of 4.64 (Highly Competent). Based on these findings, it can be concluded that the professional competence of teachers at state vocational high schools in the Padang Barat District is being demonstrated at a very high level. Therefore, teachers are expected to maintain their existing professional competence, continue to enhance their creativity in developing learning materials, and engage in continuous professional development activities to further improve the quality of instruction.